De Morgan's Laws (Logic)/Conjunction of Negations/Formulation 2/Reverse Implication

From ProofWiki
Jump to navigation Jump to search

Theorem

$\left({\neg \left({p \lor q}\right)}\right) \implies \left({\neg p \land \neg q}\right)$


Proof

By the tableau method of natural deduction:

$\vdash \left({\neg \left({p \lor q}\right)}\right) \implies \left({\neg p \land \neg q}\right)$
Line Pool Formula Rule Depends upon Notes
1 1 $\neg \left({p \lor q}\right)$ Assumption (None)
2 1 $\neg p \land \neg q$ Sequent Introduction 1 De Morgan's Laws (Logic): Conjunction of Negations: Formulation 1
3 $\left({\neg \left({p \lor q}\right)}\right) \implies \left({\neg p \land \neg q}\right)$ Rule of Implication: $\implies \mathcal I$ 1 – 2 Assumption 1 has been discharged

$\blacksquare$